Implementasi QR Code pada Pengembangan Sistem Informasi Presensi Lokakarya dan Seminar - Rangga Sidik; Khamil Aryansyah (Jurnal Manajemen Informatika (JAMIKA), 2021)
Seminars and workshops are one of the efforts to distribute knowledge from experts. In its implementation, presence is one of the vital implementation components. The activity of the seminar presence is to confirm the attendance of the participants. However, there are still implementation issues in the activities of presence confirmation for participants. The purpose of this research is to analyze, design, implement the technology of QR code to propose the new system in the activities of presence confirmation in the seminars. The research uses descriptive research method with object-oriented design approach and the prototyping model as a system development method. The research result is a web-based seminar presence information system that is expected to handle the issues with better procedures for both participant and event organizer.